INCREASING KNOWLEDGE ABOUT ORAL CARE AMONG ELEMENTARY STUDENTS IN SDN DUKUHSARI 2 JABON SIDOARJO - Diana, Meli; Qiromah, Nafidatul; Maharani, Calista; Maulani, Vitta; Nimreksu, Felicia; Oratmangun, Maria; Alfiyan; Afriyanto (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
This community service activity carried out by Poltekkes Kerta Cendekia is routine activities done by academic civities in order to improve the health quality of school-age children in the Sidoarjo Regency environment. This activity carries the theme